Studying the Artistic Composition in the Novel ”Mohal” by the Writer Youssef Zeidan - Madallah AL-Asasfeh, ALMothanna (Dirasat: Human and Social Sciences, 2022)
This research deals with the study of artistic formation through a textual reading of the novel "Mohal" by standing at the significance of the title, temporal structure, the novelist’s character, the voice of the narrator, and other narration techniques with artistic significance that represent dramatic events of an artistic nature, which distinguishes this work with reference to the significance of the place. In its novel dimensions and contents, and its role in highlighting the novelistic theme in a remarkable way.